Kontestasi Isi Berita PT Pelabuhan Indonesia I (Persero) pada Masa Covid 19 di Waspada.co.id dan Medanbisnisdaily.com Periode 3 Maret – 4 Juni 2020 - Rahmadani Harahap; Hasan Sazali; Fakhrur Rozi (Communication & Social Media, 2021)
The research entitled Contestastion of the News Content of PT Pelabuhan Indonesia I (Persero) The Covid 19 Period at Waspada.co.id and Medanbisnisdaily.com Period March 3 - June 4, 2020. This study aims to find various content from the messages quoted in Waspada Media. co.id and Medanbisnisdaily.com which published the news of PT Pelabuhan Indonesia I (Persero) to find out the direction of the news. A total of 12 news for the sample, and using descriptive analysis method with content analysis. This study found illustrations of messages in a systematic and quantitative manner. As a parameter, the category construction is used as the News Direction. The News Direction category consists of Favorable (+), Disliked (-), and Neutral (0). All categories correspond to the Harold Laswell category (Flourney, 1989: 128). Each unit of analysis is based on the frequency and character of News Content, according to predefined categories. Based on the content analysis carried out, it presents a news report about PT Pelabuhan Indonesia I (Persero) published on Waspada.co.id and Medanbisnisdaily.com for the period March 3 - June 4 2020 written in a very profitable news direction with a contribution of 84%.